The Rhizobium meliloti trpE(G) gene is regulated by attenuation, and its product, anthranilate synthase, is regulated by feedback inhibition. - Bae, Y M (1990)
In Rhizobium meliloti, the genes involved in biosynthesis of the amino acid tryptophan are found at three separate chromosomal locations. Of the three gene clusters, trpE(G), trpDC, and trpFBA, only the trpE(G) gene is regulated by the end product of the pathway, tryptophan. We found that trpE(G) mRNA contains a leader transcript that terminates at a stem-loop structure in a putative transcription attenuator. The level of this leader transcript was constant regardless of the amount of tryptophan in the growth medium. However, the level of full-length trpE(G) mRNA decreased as the amount of tryptophan increased. The beta-galactosidase activity of an R. meliloti strain carrying a trpL'-'lacZ fusion remained constant at different tryptophan concentrations, but the beta-galactosidase activity of the same strain carrying a trpE(G)'-'lacZ fusion decreased as the tryptophan concentration increased. These data indicate that transcription of the R. meliloti trpE(G) gene is regulated only by attenuation. We also found that the product of the trpE(G) gene, anthranilate synthase, is feedback inhibited by tryptophan.